Characterization of a Novel Food Grade Emulsion Stabilized by the By- Product Proteins Extracted From the Head of Giant Freshwater Prawn (Macrobrachium rosenbergii) - Wu, Yi; Li, Yufeng; Wang, Ronghan; Zhao, Yong; Liu, Haiquan; Wang, Jing Jing (Frontiers in Nutrition, 2021)
The aim of this work was to develop a food-grade emulsion that stabilized by the by-product proteins in the head of giant freshwater prawn. The physicochemical properties of protein particles were characterized, and the stability of proteins-stabilized emulsions under different environmental stresses was evaluated. Results showed that the proteins were relatively hydrophilic and preferentially resided in the aqueous phase to form oil/water emulsions. On this basis, the proteins exhibited superior ability to stabilize the emulsions, and remarkably, the emulsions stabilized by 2% proteins and 3:7 oil/water ratio efficiently resisted the freeze-thaw treatment and the change of pH (3–9), salt addition (NaCl, 50–400 mM), and storage temperatures (4–60°C). Furthermore, the emulsions showed a matched long-term stability with the existing biopolymers-stabilized emulsions. Consequently, this is the first finding of the by-product proteins in the head of giant freshwater prawn as an excellent emulsifier to stabilize emulsions, which help to improve the stability of food-grade emulsions and the added value of aquatic products.